Morphological and Histological Studies of Anogenital Scent Glands of Egyptian Jerboa Jaculus Orientalis - Abusrer, Salma A. (Al-Mukhtar Journal of Sciences, 2023)
Rodents depend on the scent glands and their chemical secretions that stimulate the behavior of the same species and other predators in natural environments. The great Egyptian jerboa Jaculus orientalis were obtained between Ajdabiya and Benghazi, eastern Libya to reveal their morphological and histological constituents. Because there are few studies on this subject, the morphological and histological details of the anogenital region glands of adult male and female Jaculus orientalis will be described in this study. The anesthetized animal with diethyl ether was dissected then the skin around the anogenital region and one-third of the anal canals were excised and fixed in 10% aldehyde formalin, dehydration, and embedded, then serially sectioned 5µm was cut, stained with eosin, hematoxylin, and trichrome for microscopic examination. A huge circumferential aggregation of modified compound branched sebaceous glands that permeate the submucous and are infused into the internal sphincter muscle layer of the anal canal, with secretory canals that drain to the anal canal orifice’s most outer. The preputial glands of male and clitoris glands of female were anatomically appeared in the form of small, separate, scattered, and different sizes of follicular glands and histologically formed compound branched acini sebaceous glands surrounded by connective tissue. However, these results may drop some light on the role of these glands in the scent-marking behaviors of males and females of Jaculus orientalis.